Pengaruh ekstrak buah cabe jawa (Piper retrofractum Vahl.) terhadap perkembangan dan mortalitas kepik hijau - Hasnah Hasnah; Alfian Rusdy (Jurnal Floratek, 2015)
The Effects of Piper retrofractum Vahl Fruit Extract On The Growth and Mortality of Green Stink BugsABSTRACT. The effects of Piper retrofractum Vahl. fruit extract on the growth and mortality of green stink bugs. Green stink bug is an important pest that attack bean pods of legumes plants since the flowering phase until the harvesting phase, resulting in a decrease in the quality and quantity of harvest. The objective of this study concentration of the fruit extract in controlling green stink bugs. Completely randomized factorial design is used in this study with eight treatment combinations consisting of two stages of green stink bug growth ( nymph and imago) and four P. retrofractum fruit extract concentration level of 3%, 6%, 9% and 12%. The research results showed that the extract of P. retrofractum is the potential to control the green stink bugs, where the concentration of 9% lead the green stink bugs, mortality reached 81.65% after 3 days after aplication (DAA). Mortality of imago and nymph, each reaches 73.35% and 83.32% at 4 DAA. Average time of green stink bugs’ mortality at a concentration of 12%, is each 2.65 days for nymph and 2.69 days for imago. In the other hand, feedeng inhibition of green stink bugs at concentration of 12% reaches 48.61 percent.